DNA sequencing based on electronic tunneling in a gold nanogap: a first-principles study. Issue 9 (22nd February 2022) - Zou, Hao; Wen, Shizheng; Wu, Xiaoyan; Wong, Ka-Wai; Yam, ChiYung
Abstract : First-principles simulations show the ability of DNA sequencing based on electronic tunneling in a sulfur-decorated gold nanogap. Abstract : Deoxyribonucleic acid (DNA) sequencing has found wide applications in medicine including treatment of diseases, diagnosis and genetics studies. Rapid and cost-effective DNA sequencing has been achieved by measuring the transverse electronic conductance as a single-stranded DNA is driven through a nanojunction. With the aim of improving the accuracy and sensitivity of DNA sequencing, we investigate the electron transport properties of DNA nucleobases within gold nanogaps based on first-principles quantum transport simulations. Considering the fact that the DNA bases can rotate within the nanogap during measurements, different nucleobase orientations and their corresponding residence time within the nanogap are explicitly taken into account based on their energetics. This allows us to obtain an average current that can be compared directly to experimental measurements. Our results indicate that bare gold electrodes show low distinguishability among the four DNA nucleobases while the distinguishability can be substantially enhanced with sulfur atom decorated electrodes. We further optimized the size of the nanogap by maximizing the residence time of the desired orientation.